Analysis of TNF-antagonist switch over time and associated risk factors in the Swiss Inflammatory Bowel Disease Cohort. (October 2014) - Hiroz, Philippe; Vavricka, Stephan R.; Fournier, Nicolas; Safroneeva, Ekaterina; Pittet, Valérie; Rogler, Gerhard; Schoepfer, Alain M.
Abstract Background and aims. Limited data from large cohorts are available on tumor necrosis factor (TNF) antagonists (infliximab, adalimumab, certolizumab pegol) switch over time. We aimed to evaluate the prevalence of switching from one TNF antagonist to another and to identify associated risk factors. Methods. Data from the Swiss Inflammatory Bowel Diseases Cohort Study (SIBDCS) were analyzed. Results. Of 1731 patients included into the SIBDCS (956 with Crohn's disease [CD] and 775 with ulcerative colitis [UC]), 347 CD patients (36.3%) and 129 UC patients (16.6%) were treated with at least one TNF antagonist. A total of 53/347 (15.3%) CD patients (median disease duration 9 years) and 20/129 (15.5%) of UC patients (median disease duration 7 years) needed to switch to a second and/or a third TNF antagonist, respectively. Median treatment duration was longest for the first TNF antagonist used (CD 25 months; UC 14 months), followed by the second (CD 13 months; UC 4 months) and third TNF antagonist (CD 11 months; UC 15 months). Primary nonresponse, loss of response and side effects were the major reasons to stop and/or switch TNF antagonist therapy. A low body mass index, a short diagnostic delay and extraintestinal manifestations at inclusion were identified as risk factors for a switch of the first used TNF antagonist within 24 months of its use in CD patients. Conclusion. Switching of the TNF antagonist over time is a common issue. The median treatment duration with a specific TNF antagonist is diminishing with an increasing number of TNF antagonists being used.